INNOVATIVE METHODS AND PEDAGOGICAL – PSYCHOLOGICAL APPROACH TO THE FORMATION OF DIGITAL LITERACY IN MODERN STUDENTS - Zilola Normurodovna Haydarova (Western European Studies, 2024)
This article reflects on the need for digital literacy, methods of innovation in the formation of digital literacy in schoolchildren and mechanisms for the formation of digital literacy in modern students in the process of digitization
Keywords: Digital teaching; digital education; digital literacy